2021
DOI: 10.3389/fonc.2021.646577
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Values of Advanced Non-Small Cell Lung Cancer Patients Harboring Uncommon EGFR Mutations—The Mutation Patterns, Use of Different Generations of EGFR-TKIs, and Concurrent Genetic Alterations

Abstract: IntroductionEpidermal growth factor receptor (EGFR) 19del and L858R mutation are known as “common mutations” in non-small cell lung cancer (NSCLC) and predict sensitivities to EGFR tyrosine kinase inhibitors (TKIs), whereas 20ins and T790M mutations confer drug-resistance to EGFR-TKIs. The role of the remaining uncommon EGFR mutations remains elusive.MethodsWe retrospectively screened a group of NSCLC patients with uncommon EGFR mutations other than 20ins and T790M. The mutation patterns, use of different gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…Another retrospective study included 102 NSCLC patients with EGFR uncommon mutations and 99 with single EGFR mutations as control group, treated with first- or second-generation EGFR TKIs as first-line treatment [ 45 ]. Of note, among patients treated with first-line EGFR TKIs, RRs in combined common plus uncommon and combined uncommon EGFR mutations were lower compared to single common EGFR mutations (objective response rate, ORR 54.5% and 44.4% vs. 75%, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another retrospective study included 102 NSCLC patients with EGFR uncommon mutations and 99 with single EGFR mutations as control group, treated with first- or second-generation EGFR TKIs as first-line treatment [ 45 ]. Of note, among patients treated with first-line EGFR TKIs, RRs in combined common plus uncommon and combined uncommon EGFR mutations were lower compared to single common EGFR mutations (objective response rate, ORR 54.5% and 44.4% vs. 75%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…No differences were observed among compound subgroups treated with second-generation afatinib. Moreover, afatinib showed higher ORR and longer PFS compared to first-generation TKIs in combined common plus uncommon mutations (ORR 100% vs. 54.5%, p = 0.017; PFS NE vs. 13.6 months, p = 0.032, respectively) [ 45 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with compound uncommon mutations have better tumor response and prognosis than patients with single uncommon mutations ( Brindel et al, 2020 ; Yamada et al, 2020 ; Yang et al, 2020 ; Passaro et al, 2021 ; Tan et al, 2021 ). In the study by Yang et al, afatinib yielded better anti-tumor activity against compound uncommon mutations than against major uncommon mutations in both TKI-naïve patients and TKI-pretreated patients ( Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different EGFR-targeted drugs have shown variable efficacy for uncommon mutations within EGFR exon 18-21 (27,28). Previous studies demonstrated that patients with uncommon EGFR mutations treated with afatinib might have a better prognosis than those treated with firstgeneration TKIs (4,7,29,30). Afatinib at 40 mg for LAD with major uncommon EGFR mutations (G719X, L861Q, and S768I) resulted in a varied PFS of 10.7-17.1 months and an ORR around 50-74% (6,31,32).…”
Section: Discussionmentioning
confidence: 99%